Wacana Kritis Lagu “Bento” Karya Iwan Fals: Representasi Ideologi Dominasi dan Kekuasaan Elit Orde Baru (Model Teun A. Van Dijk) - Salma Fiddaraini (Perspektif : Jurnal Pendidikan dan Ilmu Bahasa, 2025)
Iwan Fals’ song "Bento" offers social criticism, which is analyzed using Teun A. Van Dijk's critical discourse analysis model. Released in 1989, the song critiques the social conditions and behaviors of the wealthy elite during the New Order era, highlighting issues of arrogance, corruption, and social inequality. This qualitative descriptive study applies the Analisis Wacana Kritis (AWK) method, analyzing the lyrics of "Bento" through three dimensions: text, social cognition, and social context. In the text dimension, the analysis reveals the main theme as a depiction of the fictional character "Bento," portrayed as an arrogant and corrupt figure. The text structure employs a narrative persona pattern, with semantic elements describing the luxury of New Order rulers and the exploitation of the common people. The stylistic devices, including anthropomorphism and rhetoric, emphasize the selfish enjoyment of the elite. In the social context, the song is a response to the corruption, collusion, and nepotism (KKN) that characterized the New Order regime. Through satire, "Bento" critiques the dominance of the elite and their disregard for the common people. Overall, the song exposes the power dynamics and corruption under the New Order regime.